Stachydrine prevents LPS‐induced bone loss by inhibiting osteoclastogenesis via NF‐κB and Akt signalling. Issue 10 (21st July 2019) - Meng, Jiahong; Zhou, Chenhe; Zhang, Wenkan; Wang, Wei; He, Bin; Hu, Bin; Jiang, Guangyao; Wang, Yangxin; Hong, Jianqiao; Li, Sihao; He, Jiamin; Yan, Shigui; et al.
Abstract: Osteoclast overactivation‐induced imbalance in bone remodelling leads to pathological bone destruction, which is a characteristic of many osteolytic diseases such as rheumatoid arthritis, osteoporosis, periprosthetic osteolysis and periodontitis. Natural compounds that suppress osteoclast formation and function have therapeutic potential for treating these diseases. Stachydrine (STA) is a bioactive alkaloid isolated from Leonurus heterophyllus Sweet and possesses antioxidant, anti‐inflammatory, anticancer and cardioprotective properties. However, its effects on osteoclast formation and function have been rarely described. In the present study, we found that STA suppressed receptor activator of nuclear factor‐κB (NF‐κB) ligand (RANKL)‐induced osteoclast formation and bone resorption, and reduced osteoclast‐related gene expression in vitro. Mechanistically, STA inhibited RANKL‐induced activation of NF‐κB and Akt signalling, thus suppressing nuclear factor of activated T cells c1 induction and nuclear translocation. In addition, STA alleviated bone loss and reduced osteoclast number in a murine model of LPS‐induced inflammatory bone loss. STA also inhibited the activities of NF‐κB and NFATc1 in vivo. Together, these results suggest that STA effectively inhibits osteoclastogenesis both in vitro and in vivo and therefore is a potential option for treating osteoclast‐related diseases.